1+6(x-4)=2-8(x-9)

Simple and best practice solution for 1+6(x-4)=2-8(x-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1+6(x-4)=2-8(x-9) equation:


Simplifying
1 + 6(x + -4) = 2 + -8(x + -9)

Reorder the terms:
1 + 6(-4 + x) = 2 + -8(x + -9)
1 + (-4 * 6 + x * 6) = 2 + -8(x + -9)
1 + (-24 + 6x) = 2 + -8(x + -9)

Combine like terms: 1 + -24 = -23
-23 + 6x = 2 + -8(x + -9)

Reorder the terms:
-23 + 6x = 2 + -8(-9 + x)
-23 + 6x = 2 + (-9 * -8 + x * -8)
-23 + 6x = 2 + (72 + -8x)

Combine like terms: 2 + 72 = 74
-23 + 6x = 74 + -8x

Solving
-23 + 6x = 74 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
-23 + 6x + 8x = 74 + -8x + 8x

Combine like terms: 6x + 8x = 14x
-23 + 14x = 74 + -8x + 8x

Combine like terms: -8x + 8x = 0
-23 + 14x = 74 + 0
-23 + 14x = 74

Add '23' to each side of the equation.
-23 + 23 + 14x = 74 + 23

Combine like terms: -23 + 23 = 0
0 + 14x = 74 + 23
14x = 74 + 23

Combine like terms: 74 + 23 = 97
14x = 97

Divide each side by '14'.
x = 6.928571429

Simplifying
x = 6.928571429

See similar equations:

| (x-6)/4=20 | | 4(4+4k)=-32+8k | | -297=4+7(-5v-8) | | 10+2-21=0 | | x-6/4=20 | | ((T^2+3t-8)-(t^2-2t+6))(t-4)=0 | | 7+20x+12x= | | 3-9t=-10t | | 4X+48=8(X+6)-4X | | 252=4(-1-8v) | | -3-8p=-9p+6 | | 3a+3=9+a | | 4x-3(4-3x)=5(x-4)-40 | | Y/3=40 | | 17/6=34/x | | 2+3(x+5)=38 | | 154=7(7k+1) | | -4(n-6)=n+6 | | 5+8(x-3)=4-4(x-3) | | 4(3Z-1)-5(Z+4)=5(Z+1) | | 2/3=1/9(27) | | -27a-42=a+98 | | T/0.16=0.5/0.4 | | 110=7p-8(2-7p) | | 4(5x-4)=4x+17 | | -3-8=-9+6 | | 162=-6(1-7x) | | 19/11=q/15 | | C+212=-5c-28 | | 6s-8=1+5s | | 8(7n-4)=-480 | | 4x+3(x-9)=4(x-6) |

Equations solver categories